2020
DOI: 10.1590/1980-265x-tce-2018-0396
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Strategies Used by Women for Confronting Marital Violence

Abstract: Objective: to unveil the strategies used by women for confronting marital violence. Method: a qualitative research using the Straussian orientation of the Data Grounded Theory as a theoretical-methodological framework and two Justice Courts for Peace at Home as its scenario. Data was collected through individual interviews and analyzed in the coding process in three interdependent stages: open, axial and selective coding. Results: to elucidate the “Strategy” component, the following categories emerged: Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
(21 reference statements)
1
6
0
4
Order By: Relevance
“…In some cases, there was even an incentive to remain in the abusive context under the justification that this would guarantee financial security for the woman and her children. These results corroborate findings from studies carried out with women in situations of violence, which highlighted, among the difficulties stopping the cycle of violence, economic dependence on the partner, lack of family and/ or financial support and concern about maintaining stability for the children 20,21 . Therefore, reflecting on this stability underpins women's decision to remain with the aggressors and in the situations of marital violence, requiring concrete actions that support them in this decision.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In some cases, there was even an incentive to remain in the abusive context under the justification that this would guarantee financial security for the woman and her children. These results corroborate findings from studies carried out with women in situations of violence, which highlighted, among the difficulties stopping the cycle of violence, economic dependence on the partner, lack of family and/ or financial support and concern about maintaining stability for the children 20,21 . Therefore, reflecting on this stability underpins women's decision to remain with the aggressors and in the situations of marital violence, requiring concrete actions that support them in this decision.…”
Section: Discussionsupporting
confidence: 87%
“…In this sense, for children, breaking away from the violence suffered provides the opportunity to confer new meaning to what they have experienced, in order to avoid the reproduction of situations of violence in the future. To transform this reality, it is opportune to draw the managers' attention regarding their responsibility and incorporation of the strategies proposed by the Network to Combat Violence [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…It found that women’s groups favor female reflection and empowerment, because they provide support, care, and self-knowledge. Moreover, they make it possible to express feelings, share experiences and rethink behaviors ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the long period and the different levels of judgment may lead to withdrawing the report. Professionals in the service network are responsible for guiding women to encourage continuity of the judicial process ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In order to promote institutionalized care for women within the scope of the health services, this study shows that the professionals are responsible for the care and base their praxis on sensitive and welcoming listening, as well as offering information about their rights. National and international studies reveal that the support provided by the professionals, whether based on interpectoral referrals such as legal-police services, inclusion in an employment and income generation program, participation in reflective groups, or in other ways, contributes to women becoming stronger and leaving violent relationships [27][28][29] . This professional course of action leads to female empowerment and, consequently, favors rupture of violent relationships.…”
Section: /14mentioning
confidence: 99%